2009
DOI: 10.1111/j.1742-6723.2008.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving adherence to asthma clinical guidelines and discharge documentation from emergency departments: Implementation of a dynamic and integrated electronic decision support system†

Abstract: The use of this decision support system in patients presenting to emergency with asthma was associated with improvements in clinical documentation and discharge management plans. Electronic decision support systems developed collaboratively with clinicians should play an important part of system-wide efforts to improve guideline adherence and compliance in ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 16 publications
(33 reference statements)
1
28
0
1
Order By: Relevance
“…[5][6][7][8] Multiple quality improvement (QI) efforts to improve inpatient asthma care for children have been reported, but a positive impact on asthma outcomes is often not demonstrated. 3,[9][10][11][12][13][14][15][16][17][18] No data exist about the sustainability or long-term impact of QI interventions. Furthermore, most of the successful pediatric inpatient asthma interventions are implemented at a tertiary care pediatric centers, with little information available about dissemination to community hospitals.…”
mentioning
confidence: 99%
“…[5][6][7][8] Multiple quality improvement (QI) efforts to improve inpatient asthma care for children have been reported, but a positive impact on asthma outcomes is often not demonstrated. 3,[9][10][11][12][13][14][15][16][17][18] No data exist about the sustainability or long-term impact of QI interventions. Furthermore, most of the successful pediatric inpatient asthma interventions are implemented at a tertiary care pediatric centers, with little information available about dissemination to community hospitals.…”
mentioning
confidence: 99%
“…[16][17][18][19][20][21]23,24,31 This project did show promising results for using evidence-based flowsheets based on five of six stroke management goals, whereas the use of clinical decision support revealed insignificant results due to notable limitations. The impact of evidence-based nursing documentation flowsheets and clinical decision support reminders should continue to be measured for influence on the quality of nursing documentation and ultimately improve patient outcomes.…”
Section: Resultsmentioning
confidence: 96%
“…14 The EHR must also be optimized to incorporate standardized documentation systems with evidence-based clinical practice guidelines, clinical decision support, and other clinically important documentation variables that can assist decision making. 13,[15][16][17][18] Structured documentation templates for capturing data have also been shown to improve overall data quality by producing nursing documentation that is more complete, relevant, and comprehensive. [19][20][21] Several studies have evaluated the effectiveness of computerized documentation templates, merged with disease-specific content, to help standardize clinician documentation.…”
Section: Introductionmentioning
confidence: 99%
“…One approach for effectively integrating clinical practice guidelines into medical practice is the use of CDSS. The use of CDSS has facilitated clinicians' adherence to clinical practice guidelines, thereby improving patient outcomes (Kotze & Brdaroska, 2004;Kwok, Dinh, Dinh, & Chu, 2009). Kotze and Brdaroska (2004) noted that the "ability of computers to store, search and sort large volumes of data rapidly, as well as the everexpanding knowledge, access and use of computers, have paved the way for the incorporation of clinical practice guidelines into computer-based decision support systems" (p. 362).…”
Section: Clinical Practice Guidelinementioning
confidence: 99%
“…The encoded rules in the clinical practice guidelines provide the framework in which programming rules are encoded and used in the development of CDSS. For example, Kwok et al (2009) found that the use of an integrated and dynamic electronic decision support system (EDSS) at a single emergency department promoted strict adherence to asthma clinical guidelines and improved clinical documentation and discharge management plans for asthma management. It is in this regard that Kotze and Brdaroska (2004) indicated that CDSS are "crucial elements in long-term strategies for promoting the use of clinical practice guidelines" (p. 362).…”
Section: Clinical Practice Guidelinementioning
confidence: 99%